PERANCANGAN FASILITAS KERJA AKTIVITAS PROSES MANUAL SOLDER PADA PT XY - Siahaan, Devi Mandriana; Zetli, Sri (LPPM Universitas Putera Batam, 2021)
Humans are an important role for the development of industrial companies so companies must pay attention to the working conditions of their workers. Working conditions that require workers to stand continuously result in non-ergonomic work postures. In the work process of manual soldering activities at PT. XY is still done manually by standing for too long, this can lead to MSDs (musculoskeletal disorders) among workers. MSDs complaints can be reduced in various ways, one of which is by designing work facilities. Before designing work facilities, it is necessary to measure the complaints felt by manual soldering workers. Rapid Entire Body Assessment (REBA) is a process that develops the ergonomics section and is obtained quickly for measuring worker posture. From the results of the study by distributing the NBM questionnaire, it was found that complaints on the neck, back, shoulders, waist, thighs, knees, calves, ankles and feet. The results of the REBA score on the work posture of manual soldering activities are 4 and 5 in the medium category and need corrective action. The solution to reduce this risk requires work facilities, namely by designing work facilities, namely work chairs. The design of this work chair is adjusted to the anthropometry of the workers. Anthropometric data used are Hip Width (LP) which is taken for the width of the seat base, Sitting Elbow Height (TSD) which is taken for the height of the seat, Back Height (TP) is taken for the height of the seat back and Popliteal Butt Length (PPP). taken for the length of the chair.